2016
DOI: 10.1108/jap-03-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Policing and street triage

Abstract: In his recent report, Lord Adebowale (2013) described mental health issues as "core police business". The recent retrenchment in mental health and wider public services mean that the demands on the police in this area are likely to increase. Mental health triage is a concept that has been adapted from general and mental health nursing for use in a policing context. The overall aim of triage is to ensure more effective health outcomes and the more effective use of resources. This article examines the current po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…This also identifies that a number of different collaborative operational models may be labelled as ‘Street Triage’ [10], but could also be argued as standalone collaborative interventions for example mental health training for police offers. Our findings also support those of Irvine, Allen and Webber [29] in that Street Triage services in the UK demonstrate some crossover between crisis response typologies [26], which may suggest that further assessment of existing Street Triage operating models should be taken to develop new terminology applicable to UK services.…”
Section: Discussionmentioning
confidence: 99%
“…This also identifies that a number of different collaborative operational models may be labelled as ‘Street Triage’ [10], but could also be argued as standalone collaborative interventions for example mental health training for police offers. Our findings also support those of Irvine, Allen and Webber [29] in that Street Triage services in the UK demonstrate some crossover between crisis response typologies [26], which may suggest that further assessment of existing Street Triage operating models should be taken to develop new terminology applicable to UK services.…”
Section: Discussionmentioning
confidence: 99%
“…The participants felt that this way of working would enhance the quality of the experience for detainees accessing mental healthcare. 10,19 Training This study has shown that ambulance and paramedic workers play a pivotal role in dealing with individuals experiencing mental health problems in a community setting. Yet, training for this group of professionals is somewhat limited.…”
Section: Accessing the 136 Suitementioning
confidence: 99%
“…11,[15][16][17][18] In addition, a number of non-systematic literature reviews also described relevant intervention models. [19][20][21][22] The existing reviews incorporated overlapping literature searches, the most recent of which was completed in June 2016. Although these reviews provided a useful overview of the existing evidence, the reviews also highlighted the methodological inadequacy of many existing evaluations for drawing firm conclusions about the effects of PRMHT interventions.…”
Section: Results Of Scoping Workmentioning
confidence: 99%